Increased Vulnerability: Analysis of Gender-Based Violence (GBV) Among Internally Displaced Women in Burkina Faso - Noëlie, Kouraogo Kiswendsida; Afsata, Pare/ Kabore (Advances in Social Sciences Research Journal, 2025)
Since 2016, Burkina Faso has been spiraling into a cycle of armed violence. In 2023, 3,710 security incidents were recorded, mainly linked to the presence of non-identified armed groups. By March 31,2023, nearly 10% of the Burkinabe population, 2,062,534 people, had been displaced as a result of this escalation of violence, according to the Permanent Secretariat of the National Council for Emergency Relief and Rehabilitation (SP/CONASUR). According to the Multisectoral Needs Assessment (MSNA), in 2023, 39% of internally displaced persons had been displaced for more than two years, and 20% more than once. An increase in secondary movements was observed in 2023. According to the Rapid Response Operational Coordination Group (GCORR), between January and October 2023, 93 population movement alerts were recorded, compared to 89 alerts for the same period in the previous year. These upheavals have reshaped society, deepened vulnerabilities, and widened gender inequality The crisis has an even greater on women and girls[1], who face heightened risks of gender-based violence (GBV) in physical, sexual, and psychological forms. In this study, we analyze GBV in the context of internal displacement in Burkina Faso, asking: Does displacement increase the incidence of GBV against internally displaced women? What factors heighten their vulnerability? And how do power dynamics within displaced and host communities shape the risks they face? To answer these questions, we use a unique case study, the story of an internally displaced woman who was a victim of sexual violence and a registered resident at a center dedicated to survivors of GBV. Our approach is therefore qualitative. Through this unique case study, we aim to contribute to a better understanding of GBV in the context of internal displacement, and to more effective mechanisms for addressing it. [1] Women represent 51.7% of the population of Burkina Faso, according to the National Institute of Statistics and Demography (INSD), 2020.